Synthesis using prospective meta-analysis to reduce youths’ e-cigarette use (SPARKE): a protocol for an individual participant data prospective meta-analysis (IPD PMA) examining interventions for the prevention of youth e-cigarette use - Emily Banks; Luke Wolfenden; Melissa A Little; Sam McCrabb; Rebecca K Hodder; Kylie E Hunter; Andrew Milat; Bonnie Halpern-Felsher; Nicola Newton; Lauren A Gardner; Serene Yoong; Sion Kim Harris; et al. (BMJ Open)
Introduction Youth electronic cigarette (e-cigarette) use is a global health challenge, with multiple jurisdictions wrestling with appropriate responses, in the face of limited evidence available on effective interventions. Identifying and synthesising evidence on the effects of interventions to prevent youth e-cigarette use is required to inform prevention-focussed health policy and practice.Methods and analysis We plan to undertake an individual participant data (IPD) prospective meta-analysis (PMA). We will conduct systematic searches to identify eligible planned or ongoing randomised controlled trials (RCTs) using trial registries via WHO ICTRP and ClinicalTrials.gov and databases Medline, Embase, CENTRAL, PsycINFO, Web of Science, CINAHL and Europe PMC. We will also search grant websites for additional studies. We will include any RCT of e-cigarette and cigarette prevention interventions for youth including non-smoking and non-vaping youth aged 10 to 19 years, with no intervention, waitlist, usual care or active control. Primary outcomes will be measures of current or ever e-cigarette use. Secondary outcomes include measures of current and ever cigarette (conventional cigarette) use.Investigators from relevant trials will be invited to join the Synthesis using Prospective meta-Analysis to Reduce youths’ E-cigarette use (SPARKE) consortium prior to trial outcomes being known using harmonised methods. They are then asked to share their data within 12 months of trial completion.The primary outcomes will be analysed in a two-stage IPD meta-analysis model under an intention-to-treat framework. First, effect estimates and variances will be calculated for each trial with log-binomial regression models adjusting for key prognostic factors. For cluster RCTs, a nested random effect will be specified within trials to account for correlations within clusters. Second, effect estimates will be combined across trials in a random treatment effect, inverse variance meta-analysis model. Effect estimates will be reported as relative risk ratios with 95% CIs.Discussion This study aims to generate and expedite the synthesis of data regarding prevention interventions for adolescent e-cigarette use to inform real-world decision making. Findings will be of interest to key stakeholders, including policy makers and research funders.Ethics and dissemination Each trial will be responsible for obtaining their own ethics approval. While secondary analysis of data does not usually require ethics approval, we have received cross-institutional ethics approval from the University of Sydney (2023/714) and the University of Newcastle (H-2023–0389).